SEffEst: Effort estimation in software projects using fuzzy logic and neural networks - Israel González-Carrasco; Ricardo Colomo-Palacios; José Luis López-Cuadrado; Francisco José García Peñalvo (International Journal of Computational Intelligence Systems, 2012)
Academia and practitioners confirm that software project effort prediction is crucial for an accurate software project management. However, software development effort estimation is uncertain by nature. Literature has developed methods to improve estimation correctness, using artificial intelligence techniques in many cases. Following this path, this paper presents SEffEst, a framework based on fuzzy logic and neural networks designed to increase effort estimation accuracy on software development projects. Trained using ISBSG data, SEffEst presents remarkable results in terms of prediction accuracy.